Improving Storage Technique Coffee Green Beans and Application of Digital Management Business in “Tri Guna Karya” Catur Village, Kintamani, Bangli - I Gede Pasek Mangku; I Gde Suranaya Pandit; Ni Luh Putu Indiani; Tridtitanakiat, Pavalee Chompoorat (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Coffee is the most popular and traded drink in the world. The cultivar, environmental conditions, and agricultural management determine the physical quality, coffee taste, and chemical composition of coffee beans. The purpose of this community service was to improve the knowledge and skill level of the Triguna Karya group in terms of the technique of green bean storage; therefore, the quality and safety of the green beans can be maintained. Moreover, to increase the marketing skill strategy using a number of social media. The method used was survey, observation, mentoring, knowledge transfer, practice, documentation, and evaluation. The result showed that the group of Triguna Karya stored green coffee beans poorly in the warehouse, even though they have known postharvest handling and processing of coffee well. The group did not use temperature and humidity control during storage of green beans; therefore, they can be damaged and decrease in quality and safety. In general, the participant have understood about Facebook but less in how to use the Instagram and TikTok applications. Contribution to Sustainable Development Goals (SDGs): SDG 2: Zero HungerSDG 12: Responsible Consumption and ProductionSDG 8 : Decent Work and Economic Growth